Design and Integration of an Air Releasable Autonomous Unmanned Ground Vehicle - Okumus, Faruk Fazh; Celikol, Mert; Hasancebi, Ismet Can; Uzunoglu, Mucteba; Kirli, Ahmet (IEEE, 2019)
In situations where the aircraft has limited capability in accessing to a target point, we can benefit from the cooperation of it with a ground vehicle. This system can be used in applications of many different areas such as space exploration, defense, search & rescue, and commercial delivery. Mostly minimalist mechanical designs that may provide fulfilling certain tasks are pursued in these applications. In this study we focus on developing two main parts of the system through simulations. The airdrop of the Unmanned Ground Vehicle (UGV) to achieve a landing that can guarantee no damage on both the vehicle and the payload and an acceptable range of targeting onto the impact point is studied. Also, upon landing, the control system that can lead the vehicle to have an autonomous drive over an open terrain is designed. The simulation results confirm that the tasks associated with both stages can be conducted in convenience.
Keywords: Unmanned Ground Vehicle; Unmanned Aerial Vehicle; Autonomous driving; Aero breaking; Engineering